Biochar and straw amendments drive microbial regulation of phosphorus dynamics in saline-irrigated cotton fields - Ye, Yang; Guo, Xiaowen; Li, Yueyao; Min, Wei; Guo, Huijuan (Frontiers in Microbiomes, 2025)
Saline water drip irrigation is a potential solution for addressing freshwater scarcity in arid regions. However, prolonged use can accumulate soil salinity and reduce phosphorus (P) availability. Biochar and straw amendments have been shown to alleviate these effects, but their mechanisms in regulating microbial genes involved in P transformation under long-term saline irrigation remain unclear. This study aimed to evaluate the impact of biochar and straw incorporation on soil microbial community structure and P availability in saline-irrigated cotton fields. Based on a 14-year field trial, three treatments were developed: saline water irrigation alone (CK), saline water irrigation with biochar (BC), and saline water irrigation with straw (ST). Results indicated that both amendments significantly enhanced soil water content, organic carbon, total P, available P, and inorganic P fractions (Ca10-P, Al-P, Fe-P, and O-P) while reducing soil electrical conductivity and Ca2-P and Ca8-P fractions. Biochar increased the relative abundance of Chloroflexi, Gemmatimonadetes, and Verrucomicrobia, while straw promoted Proteobacteria and Planctomycetota. Both treatments decreased the abundance of several P mineralization genes (e.g., phoD, phoA) and increased genes associated with P solubilization (e.g., gcd). Microbial populations and P cycling genes were shown to be tightly associated with soil characteristics, with Ca2-P and Al-P serving as important mediators, according to correlation studies. Generally, under long-term salty irrigation, biochar, and straw amendments reduced soil salinity, raised soil P availability, decreased the expression of phosphorus cycling-related microbial genes, and improved soil characteristics. These results made them excellent techniques for sustainable soil management.